Bistriopelma fabianae, a new species of tarantula (Araneae: Theraphosidae: Theraphosinae) in a Queñua forest from southern Peru - Quispe-Colca, Oscar Magdiel (2020)
A new species of Bistriopelma Kaderka 2015, Bistriopelma fabianae sp. nov., from the Arequipa region in southern Peru is described, diagnosed, and illustrated. Specimens were found in a Queñua forest (Polylepis rugulosa Bitter) spread out on the slopes of Pichu Pichu volcano in the buffer zone of Salinas and Aguada Blanca National Reserve. Biological and ecological data of B. fabianae sp. nov. are provided as well as notes on B. kiwicha and B. peyoi, two new species recently described from Apurimac and Cusco regions. Publicación registrada en Zoobank/ZooBank article registered:LSIDurn:lsid:zoobank.org:pub:BB9DF4D9-6684-46AF-9D15-71FEC64CD032Acto nomenclatural/nomenclatural act:Bistriopelma fabianae Quispe-Colca and Kaderka, 2020LSIDurn:lsid:zoobank.org:act:B63485CD-C00D-4E93-AF02-914AD9A566DA